2017
DOI: 10.24820/ark.5550190.p009.824
|View full text |Cite
|
Sign up to set email alerts
|

The influence of salt additives on the macrocyclic product distributions in double-amidation reactions

Abstract: We present an improvement of our own method for synthesising macrocyclic compounds via doubleamidation reactions of aromatic dimethyl esters with five oxa-aliphatic α,ω-diamines of different lengths, leading to a large library of potential ion receptors. We studied the influence of various inorganic salts (NaCl, KCl, CsCl, NH4Cl, MgSO4, CaCl2, CuSO4) on the macrocyclization reaction. The results were analyzed in terms of substrate conversion and distribution of products, using high performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…We recently demonstrated that inorganic salts have a great impact on the formation of macrocyclic benzoamides via the double-amidation reaction of methyl dicarboxylic esters with α,ω-diamines. 52 On the basis of these results, herein we investigate the distribution of the macrocyclic products of this reaction, namely, macrocyclic diamides and tetraamides, in two-, three-, and four-substrate CLs formed under atmospheric and high-pressure conditions. To study these processes, we chose two chemsets of substrates, i.e., methyl dicarboxylic esters (chemset 1 ) and α,ω-diamino ethers (chemset 2 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that inorganic salts have a great impact on the formation of macrocyclic benzoamides via the double-amidation reaction of methyl dicarboxylic esters with α,ω-diamines. 52 On the basis of these results, herein we investigate the distribution of the macrocyclic products of this reaction, namely, macrocyclic diamides and tetraamides, in two-, three-, and four-substrate CLs formed under atmospheric and high-pressure conditions. To study these processes, we chose two chemsets of substrates, i.e., methyl dicarboxylic esters (chemset 1 ) and α,ω-diamino ethers (chemset 2 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The composition of each library was analyzed by reversed-phase HPLC utilizing a recently reported procedure and the collection of macrocyclic products shown in Figure 4 . 52 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations